Trilobites and agnostids from the Goyder Formation (Cambrian Series 3, Guzhangian; Mindyallan), Amadeus Basin, central Australia - Smith, Patrick M.; Paterson, John R.; Brock, Glenn A. (Zootaxa, 2018)
A new assemblage containing twenty-two species of trilobites and agnostids is described from the Goyder Formation (Cambrian Series 3) in the Ross River Syncline and Gardiner Ranges of the Amadeus Basin, Northern Territory, central Australia. New trilobite taxa described include the genus, Trephina gen. nov., and four new species Adelogonus prichardi sp. nov., Hebeia stewarti sp. nov., Liostracina joyceae sp. nov., and Trephina ranfordi sp. nov. Two agnostid taxa previously known only from Antarctica, Ammagnostus antarcticus Bentley, Jago & Cooper, 2009 and Hadragnostus helixensis Jago & Cooper, 2005, are also documented. Of the two agnostid species, the latter is the most age diagnostic, previously reported from the Cambrian Series 3 (Guzhangian; late Mindyallan; Glyptagnostus stolidotus Zone) Spurs Formation in Northern Victoria Land. This age for the Goyder Formation assemblage is supported by the co-occurrence of the trilobites Biaverta reineri Öpik, 1967, Blackwelderia repanda Öpik, 1967, Henadoparia integra Öpik, 1967, Monkaspis cf. travesi (Öpik, 1967), Nomadinis pristinus Öpik, 1967, Paraacidaspis? priscilla (Öpik, 1967), and Polycyrtaspis cf. flexuosa Öpik, 1967, also known from the late Mindyallan (G. stolidotus Zone) successions of the neighbouring Georgina Basin (Northern Territory and Queensland). The generic assemblage of the Goyder Formation is also similar to those from the Guzhangian (Mindyallan) of other parts of Australia (New South Wales, South Australia, and Western Australia), in addition to East Antarctica and North and South China.